Effectiveness Of Variative Approaches In Developing Students' Creative Abilities - Husniddin TOJIEV (Global Scientific Publishing, 2025)
In the modern educational process, great attention is paid to improving the didactic system of promising and preparing for future teachers. This article also analyzes pedagogical views aimed at improving the methodology for teaching students in colorively in the educational process. The study serves to develop independent thinking skills through the study of modern educational methods and efficiency
Keywords: education; variability; methodology; effectiveness